All-inorganic perovskite nanocrystalline composite material and preparation method and application thereof
By synthesizing all-inorganic perovskite nanocrystal composite CsPbBr3/ZnS under air conditions, the microsphere attachment structure is used to improve the stability and pressure sensitivity of the material, and the problems of insufficient stability and narrow pressure sensitivity range of existing materials are solved. Efficient and accurate pressure sensing is achieved.
Patent Information
- Application Number
- CN202411593330.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The existing pressure-sensitive fluorescent materials have insufficient stability, a narrow pressure-sensitive range and slow response speed, which cannot meet the needs of optical pressure sensors.
The all-inorganic perovskite nanocrystal composite CsPbBr3/ZnS was synthesized under air conditions by thermal injection method, and the stability and pressure sensitivity of the material were improved through the microsphere attachment structure.
It significantly improves the stability and pressure sensitivity of the material. It is suitable for optical pressure sensors in low-pressure areas, with fast response speed and high accuracy.
Smart Images

Figure CN119463869A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of luminescent materials, and in particular to an all-inorganic perovskite nanocrystalline composite material and a preparation method and application thereof. Background Art
[0002] Perovskite is a crystalline material with a molecular formula of ABX3 and an octahedral shape, in which the A position is an organic amine or inorganic cation with a large ionic radius (CH3NH 3+ , CH(NH2)2 + , Cs + ), the B position is a metal cation with a smaller ionic radius (Pb 2 + , Sn 2+ ,Ge 2+ ,Bi 3+ , Sb 3+ etc.), X is an oxygen ion or a halogen anion (Cl - ,Br - , I - ). The A-site cations and 12 X-coordinating anions form the most compact cubic stacking, which mainly plays a role in stabilizing the perovskite structure; the B-site cations combine with 6 X-coordinating anions and occupy the octahedral center. Due to the variability of valence, the B-site cations have also become the main component that determines the structure type and material properties of perovskites. According to the different A-site elements, perovskites can be divided into organic-inorganic hybrid perovskites and pure inorganic perovskites. Compared with organic-inorganic hybrid perovskites, due to Cs + With the right size to occupy the A site, all-inorganic perovskites have higher thermal stability.
[0003] As a unique thermodynamic parameter, pressure has become a key means to regulate the structure and properties of materials. Research on pressure regulation of material properties has received increasing attention from researchers at home and abroad. In recent years, with the continuous advancement and improvement of high-pressure experimental equipment, people can deeply explore the physical and chemical properties of substances under different pressure conditions, which has greatly promoted our understanding of material structure, band gaps, and kinetic processes in extreme environments. The structural characteristics and optoelectronic properties of perovskite nanocrystals show extremely high sensitivity to the response of material composites and external pressures. So far, pressure-sensitive materials have been widely used. At present, Al2O3:Cr 3+ (Ruby) and SrB4O7:Sm 2+Compounds are the most commonly used high-pressure calibration luminescent materials, with pressure sensitivities of 0.37nm / GPa and 0.26nm / GPa, respectively. However, their sensitivity to pressure is low and cannot meet the needs of optical pressure sensors. When the temperature is higher than 300℃, the two adjacent R1 and R2 lines become broadened, and the double peaks overlap and are difficult to distinguish, which reduces the accuracy of pressure measurement. Moreover, the same broadening occurs under non-hydrostatic conditions, making pressure measurement unreliable. Rare earth ion doped high-pressure calibration luminescent materials have become an effective method to improve pressure sensitivity, but they are not suitable for accurate measurement of low pressures, because below 3GPa, the fluorescence peak position varies greatly with pressure, and most organic compounds and various soft materials may undergo pressure-induced phase transitions and various physical and chemical changes. The reported pure CsPbBr3 nanocrystals are more sensitive to pressure than commonly used calibration luminescent materials, indicating that perovskite nanocrystals have broad application prospects in the field of new pressure-sensitive materials, but their pressure sensitivity and stability are still lacking. Therefore, it is necessary to develop and prepare new pressure-sensitive fluorescent materials with a wider pressure sensitivity range, faster response speed and higher accuracy. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide an all-inorganic perovskite nanocrystal composite material and a preparation method and application thereof, so as to solve the problems of insufficient stability, narrow pressure sensitive range, slow response speed, etc. of existing pressure-sensitive fluorescent materials.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] A method for preparing an all-inorganic perovskite nanocrystalline composite material comprises the following steps:
[0007] (1) firstly mixing lead bromide and octadecene for a first heat treatment, and then adding oleic acid and oleylamine for a second heat treatment to obtain a lead bromide precursor solution;
[0008] (2) mixing the lead bromide precursor solution obtained in step (1) with the cesium oleate solution to react, and cooling to obtain an all-inorganic perovskite nanocrystal mixed solution;
[0009] (3) The all-inorganic perovskite nanocrystal mixed solution obtained in step (2) is mixed with zinc stearate and dodecanethiol for reaction, centrifuged, and the solvent is removed to obtain a product.
[0010] The beneficial effects of the present invention are as follows: the present invention abandons the reliance of the traditional double-row tubes on inert gas protection, and successfully synthesizes a stable all-inorganic perovskite nanocrystalline composite material CsPbBr3 / ZnS under air conditions by adopting a hot injection method. The method is simple to operate, highly reproducible, clean and pollution-free, and is suitable for large-scale production.
[0011] Furthermore, in step (1), the mass volume ratio of lead bromide, octadecene, oleic acid and oleylamine is 0.06-0.08 g:4-6 mL:0.4-0.6 mL:0.4-0.6 mL.
[0012] Preferably, in step (1), the mass volume ratio of lead bromide, octadecene, oleic acid and oleylamine is 0.069 g: 5 mL: 0.5 mL: 0.5 mL.
[0013] Furthermore, the first heat treatment in step (1) is carried out at 100-150° C. for 30-90 min; and the second heat treatment is carried out at 100-150° C. until the lead bromide is completely dissolved.
[0014] Preferably, the first heat treatment in step (1) is carried out at 120° C. for 60 min; and the second heat treatment is carried out at 120° C. until the lead bromide is completely dissolved.
[0015] Furthermore, the cesium oleate solution in step (2) is prepared by the following method: cesium carbonate, octadecene and oleic acid are mixed and heat-treated to obtain the cesium oleate solution.
[0016] Furthermore, the mass volume ratio of cesium carbonate, octadecene and oleic acid is 0.3-0.5 g:10-30 mL:1-2 mL.
[0017] Preferably, the mass volume ratio of cesium carbonate, octadecene and oleic acid is 0.407 g:20 mL:1.25 mL.
[0018] Furthermore, the heat treatment conditions are: firstly keep the temperature at 110-130°C for 30-90 minutes, and then keep the temperature at 140-160°C until the cesium carbonate is completely dissolved.
[0019] Preferably, the heat treatment conditions are: firstly keep the temperature at 120° C. for 60 min, and then keep the temperature at 150° C. until the cesium carbonate is completely dissolved.
[0020] Furthermore, in step (2), the volume ratio of the lead bromide precursor solution to the cesium oleate solution is 4-8:0.1-0.3; the conditions for the mixed reaction are: firstly heating the lead bromide precursor solution to 180-190°C, keeping the temperature for 3-7 minutes, and then adding the cesium oleate solution to react for 30-90 seconds.
[0021] Preferably, the conditions for the mixed reaction are: firstly, the lead bromide precursor solution is heated to 185° C., kept warm for 5 minutes, and then the cesium oleate solution is added to react for 60 seconds.
[0022] Furthermore, in step (3), the mass volume ratio of the all-inorganic perovskite nanocrystal mixed solution, zinc stearate and dodecanethiol is 5-10 mL: 100-120 mg: 1-5 mL.
[0023] An all-inorganic perovskite nanocrystal composite material is prepared by adopting the preparation method.
[0024] The beneficial effects of the present invention are as follows: the active ingredient of the all-inorganic perovskite nanocrystalline composite material prepared by the present invention is a heterojunction structure composite material to which zinc sulfide microspheres are attached, which has good stability, significantly enhanced sensitivity to pressure, and excellent sensitivity under low pressure.
[0025] Application of the above all-inorganic perovskite nanocrystal composite material in the preparation of pressure detectors.
[0026] The beneficial effects of the present invention are as follows: the all-inorganic perovskite nanocrystal composite material prepared by the present invention can be applied to the field of pressure sensing, has excellent sensitivity even under low pressure, can be used for optical pressure sensors with a measurement range of less than 3GPa, and has potential application value in the field of detecting electrical conductivity under crustal pressure, which is of great significance for the preparation of a new type of luminous pressure gauge with fast response speed and high accuracy in low-pressure areas.
[0027] The present invention has the following beneficial effects:
[0028] (1) The present invention overcomes the limitations faced by the original hot injection method when synthesizing perovskite nanocrystals under nitrogen conditions. By adopting a new synthesis strategy, it is possible to synthesize high-quality all-inorganic perovskite nanocrystal composite materials in air. It is easy to operate, has strong reproducibility, and is suitable for actual large-scale production.
[0029] (2) Compared with pure all-inorganic perovskite nanocrystal materials, the all-inorganic perovskite nanocrystal composite material prepared by the present invention significantly improves the luminescence intensity of the attached structure and presents a brighter and more stable luminescence effect. The photoluminescence intensity of the microsphere attached heterostructure in the pressure range of 0 to 0.29 GPa is significantly improved, indicating that the introduction of microspheres not only significantly improves the luminescence kinetics of the all-inorganic perovskite nanocrystal material, but also prolongs its luminescence lifetime, effectively broadening the application range of perovskite nanocrystals under high pressure environments.
[0030] (3) The all-inorganic perovskite nanocrystal composite material prepared by the present invention improves its responsiveness to pressure by modifying the all-inorganic perovskite nanocrystal material through microsphere attachment to form a microsphere attachment structure. It also has excellent sensitivity under low pressure and can be used for optical pressure sensors with a measurement range of less than 3 GPa. It also has potential application value in the field of detecting conductivity under crustal pressure, and is of great significance for the preparation of a new type of luminescent pressure gauge with fast response speed and high accuracy in low-pressure areas. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The XRD spectrum of the all-inorganic perovskite nanocrystalline composite material prepared in Example 1;
[0032] Figure 2 This is a microscopic morphology of the all-inorganic perovskite nanocrystalline composite material prepared in Example 1;
[0033] Figure 3 The fluorescence lifetime decay diagram of the all-inorganic perovskite nanocrystal composite material prepared in Example 1 and the existing mechanoluminescent material;
[0034] Figure 4 This is a graph showing the variation of the central wavelength of the photoluminescence spectrum of the all-inorganic perovskite nanocrystal composite material prepared in Example 1 under pressure excitation with pressure. DETAILED DESCRIPTION
[0035] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] Embodiment 1:
[0037] A method for preparing an inorganic perovskite nanocrystalline composite material comprises the following steps:
[0038] (1) Under vacuum conditions, 0.069 g of lead bromide and 5 mL of octadecene are mixed, dried at 120° C. under vacuum conditions for 1 h, and then 0.5 mL of oleic acid and 0.5 mL of oleylamine are injected, and the mixture is kept warm at 120° C. until the lead bromide is completely dissolved in the octadecene, thereby obtaining a lead bromide precursor solution;
[0039] (2) Under vacuum conditions, 0.407 g of cesium carbonate, 20 mL of octadecene and 1.25 mL of oleic acid were mixed, dried in a vacuum drying oven at 120° C. for 1 h, then heated to 150° C. and kept warm for 12 h until the cesium carbonate was completely dissolved, thereby obtaining a cesium oleate precursor solution;
[0040] (3) raising the temperature of the lead bromide precursor solution obtained in step (1) to 185° C., keeping the temperature for 5 min, and then quickly injecting 0.2 mL of cesium oleate precursor solution. After reacting for 60 s, the beaker was quickly placed in an ice water bath to cool, thereby obtaining an all-inorganic perovskite nanocrystal solution;
[0041] (4) Under vacuum conditions, 114 mg of zinc stearate was first added to the all-inorganic perovskite nanocrystal solution obtained in step (3), and the mixture was stirred until the zinc stearate was fully dissolved. Then, 3 mL of dodecanethiol was added and stirred thoroughly, and the mixture was centrifuged and evaporated to remove the solvent to obtain an inorganic perovskite nanocrystal composite material CsPbBr3 / ZnS.
[0042] Embodiment 2:
[0043] A method for preparing an inorganic perovskite nanocrystalline composite material comprises the following steps:
[0044] (1) Under vacuum conditions, 0.060 g of lead bromide and 5 mL of octadecene are mixed, dried at 120° C. under vacuum conditions for 1 h, and then 0.5 mL of oleic acid and 0.5 mL of oleylamine are injected, and the mixture is kept warm at 120° C. until the lead bromide is completely dissolved in the octadecene, thereby obtaining a lead bromide precursor solution;
[0045] (2) Under vacuum conditions, 0.30 g of cesium carbonate, 20 mL of octadecene and 1.25 mL of oleic acid were mixed, dried in a vacuum drying oven at 120° C. for 1 h, then heated to 150° C. and kept warm for 12 h until the cesium carbonate was completely dissolved, thereby obtaining a cesium oleate precursor solution;
[0046] (3) raising the temperature of the lead bromide precursor solution obtained in step (1) to 185° C., keeping the temperature for 5 min, and then quickly injecting 0.25 mL of cesium oleate precursor solution. After reacting for 60 s, the beaker was quickly placed in an ice water bath to cool, thereby obtaining an all-inorganic perovskite nanocrystal solution;
[0047] (4) Under vacuum conditions, 110 mg of zinc stearate was first added to the all-inorganic perovskite nanocrystal solution obtained in step (3), and the mixture was stirred until the zinc stearate was fully dissolved. Then, 2 mL of dodecanethiol was added and stirred thoroughly, and the mixture was centrifuged and evaporated to remove the solvent to obtain an inorganic perovskite nanocrystal composite material CsPbBr3 / ZnS.
[0048] Embodiment 3:
[0049] A method for preparing an inorganic perovskite nanocrystalline composite material comprises the following steps:
[0050] (1) Under vacuum conditions, 0.080 g of lead bromide and 5 mL of octadecene are mixed, dried at 120° C. under vacuum conditions for 1 h, and then 0.5 mL of oleic acid and 0.5 mL of oleylamine are injected, and the mixture is kept warm at 120° C. until the lead bromide is completely dissolved in the octadecene, thereby obtaining a lead bromide precursor solution;
[0051] (2) Under vacuum conditions, 0.50 g of cesium carbonate, 20 mL of octadecene and 1.25 mL of oleic acid were mixed, dried in a vacuum drying oven at 120° C. for 1 h, then heated to 150° C. and kept warm for 12 h until the cesium carbonate was completely dissolved, thereby obtaining a cesium oleate precursor solution;
[0052] (3) raising the temperature of the lead bromide precursor solution obtained in step (1) to 185° C., keeping the temperature for 5 min, and then quickly injecting 0.15 mL of cesium oleate precursor solution. After reacting for 60 s, the beaker was quickly placed in an ice water bath to cool, thereby obtaining an all-inorganic perovskite nanocrystal solution;
[0053] (4) Under vacuum conditions, 120 mg of zinc stearate was first added to the all-inorganic perovskite nanocrystal solution obtained in step (3), and the mixture was stirred until the zinc stearate was fully dissolved. Then, 4 mL of dodecanethiol was added and stirred thoroughly, and the mixture was centrifuged and evaporated to remove the solvent to obtain an inorganic perovskite nanocrystal composite material CsPbBr3 / ZnS.
[0054] Comparative Example 1:
[0055] A method for preparing an inorganic perovskite nanocrystalline composite material comprises the following steps:
[0056] (1) Under vacuum conditions, 0.0216 g of neodymium bromide and 0.5 mL of oleic acid were mixed, and then heated at 60° C. under vacuum conditions for 24 h until the neodymium bromide was completely dissolved to obtain a neodymium bromide precursor solution;
[0057] (2) Under vacuum conditions, 0.814 g of cesium carbonate, 40 mL of octadecene and 2.5 mL of oleic acid were mixed, dried in a vacuum drying oven at 120° C. for 1 h, then heated to 150° C. and kept warm for 14 h until the cesium carbonate was completely dissolved to obtain a cesium oleate precursor solution, which was stored at 120° C. for later use;
[0058] (3) Under vacuum conditions, 0.069 g of lead bromide was dissolved in 5 mL of octadecene and dried in a vacuum drying oven at 120° C. for 1 h to obtain a lead precursor solution. 0.5 mL of the neodymium bromide precursor solution obtained in step (1) and 0.5 mL of oleic acid were quickly injected into the lead precursor solution. After the temperature was raised to 120° C. to form a uniform mixed solution, it was heated to 185° C. and kept warm for 5 min. Then, 0.4 mL of cesium oleate precursor solution was quickly injected. After reacting for 60 s, the beaker was quickly placed in an ice water bath to cool and obtain an inorganic perovskite nanocrystal solution. Centrifugation was performed and the solvent was evaporated to obtain an inorganic perovskite nanocrystal composite material CsPbBr3:Nd. The final centrifuged product was stored in hexane.
[0059] Experimental Example 1:
[0060] The inorganic perovskite nanocrystalline composite material prepared in Example 1 was characterized by XRD. The experimental results are as follows: Figure 1 shown.
[0061] Depend on Figure 1 It can be seen that the XRD pattern of the inorganic perovskite nanocrystalline composite material prepared in Example 1 of the present invention has the same characteristics as the PDF card (PDF#54-0752) of CsPbBr3, indicating that the synthesized sample has the same crystal structure as CsPbBr3. The peaks at 27.2° and 28.3° are identified as typical wurtzite ZnS (PDF#75-1534), corresponding to the (100) crystal plane and the (002) crystal plane.
[0062] Experimental Example 2:
[0063] The inorganic perovskite nanocrystalline composite material prepared in Example 1 was characterized by SEM surface morphology. The experimental results are as follows: Figure 2 shown.
[0064] The CsPbBr3 / ZnS microsphere attachment structure prepared in Example 1 is a regular rectangular parallelepiped with a uniform cubic morphology, an average diameter of 6±1 nm, and a lattice spacing of 0.58 nm on the (100) crystal plane of the CsPbBr3 nanocrystal. The red circle represents the ZnS nanoparticles attached to the surface of the CsPbBr3 nanocrystal, forming a high-quality microsphere attachment structure.
[0065] Experimental Example 3:
[0066] The inorganic perovskite nanocrystal composite material prepared in Example 1 and the existing mechanoluminescent material CsPbBr3:Nd (Comparative Example 1) were characterized by time-resolved spectroscopy, with a pulse width of 68ps and a repetition frequency of 10MHz. The experimental results are shown in Figure 3 As shown, the decay trajectory was fitted by double exponential decay kinetics, and the fitting parameters are shown in Table 1.
[0067] Table 1 Time-resolved spectral fitting data
[0068] Material Name <![CDATA[τ1]]> <![CDATA[τ2]]> <![CDATA[τ avg ]]> <![CDATA[A1]]> <![CDATA[A2]]> <![CDATA[CsPbBr3:Nd]]> 1.016 3.706 1.73 2.702 0.269 <![CDATA[CsPbBr3 / ZnS]]> 4.343 19.277 14.89 0.87 0.471
[0069] τ1 is the short lifetime generated by direct radiative transition of band edge exciton state, and τ2 is the long lifetime of non-radiative transition generated by the existence of surface defect state. A1 and A2 represent the contribution fraction of short lifetime and long lifetime to the average lifetime respectively. 3+ The fluorescence lifetime of doped CsPbBr3 nanocrystals is slightly longer than that of pure CsPbBr3 nanocrystals. Figure 3 The figure shows a comparison between the CsPbBr3:Nd nanocrystals with better fluorescence lifetime and the CsPbBr3 / ZnS microsphere attachment structure.
[0070] The results show that the lifespan of the CsPbBr3 / ZnS microsphere attachment structure prepared in Example 1 of the present invention is longer than that of the CsPbBr3:Nd nanocrystals. The average lifespan of the CsPbBr3 / ZnS microsphere attachment structure is 14.89ns, which is 8.6 times the average lifespan (1.73ns) of the CsPbBr3:Nd nanocrystals. The increase in the average lifespan of the CsPbBr3 / ZnS microsphere attachment structure reflects that the addition of ZnS reduces the degree of quantum confinement, which enhances the rate of electron transition from high energy level to low energy level. At the same time, the fast exciton capture process associated with defects is suppressed, thereby increasing the average lifespan. In addition, the contribution of A2 in the CsPbBr3 / ZnS microsphere attachment structure increases, indicating that a strong bond is formed between the CsPbBr3 nanocrystals and the ZnS nanoparticles through Pb and S, and electronic interactions are carried out. The enhanced electronic interactions lead to an increase in defect centers, and the substantial increase in τ2 also just illustrates this problem. The enhancement of fluorescence lifetime is conducive to the separation of carriers, increases the probability of photogenerated charges participating in photocatalytic reactions, and has significant advantages in improving photocatalytic efficiency, optimizing the performance of optoelectronic devices, and broadening the application fields. These advantages make the inorganic perovskite nanocrystal composite material prepared by the present invention have broad application prospects in the fields of energy, information display, biomedicine, etc.
[0071] Experimental Example 4:
[0072] The inorganic perovskite nanocrystal composite material prepared in Example 1 was used to construct a pressure sensor for pressure calibration detection. The change of the central wavelength of the luminescence spectrum under pressure is shown in the following figure. Figure 4 shown.
[0073] The experimental results show that as the pressure increases, the wavelength shows a continuous red shift phenomenon. When the pressure increases to above 2.38 GPa, the fluorescence peak of the CsPbBr3 / ZnS microsphere attachment structure is quenched. As the pressure increases, the central wavelength of the CsPbBr3 / ZnS microsphere attachment structure hardly changes within the pressure range of 0 to 0.29 GPa, but gradually shifts to a longer wavelength within the pressure range of 0.29 to 2.38 GPa.
[0074] In summary, the present invention abandons the dependence of the traditional double-row tube on inert gas protection, and successfully synthesizes a stable CsPbBr3 / ZnS microsphere attachment structure composite material under air conditions by adopting the hot injection method. The method is simple to operate, highly reproducible, clean and pollution-free, and is suitable for large-scale production. The experimental results show that compared with pure CsPbBr3 nanocrystals, the sensitivity of the CsPbBr3 / ZnS microsphere attachment structure to pressure is significantly enhanced. The maximum absolute sensitivity of the inorganic halide perovskite CsPbBr3 nanocrystal reported is 5.35nm / GPa, and the maximum sensitivity is 3.72nm / GPa. The maximum absolute sensitivity of the microsphere attachment structure of the present invention is 9.59nm / GPa, and the maximum sensitivity is 6.07nm / GPa, which has a significant enhancement in sensitivity to pressure. The pressure sensitivity of the material directly determines the performance of the sensor. Highly sensitive materials can detect small pressure changes more accurately, thereby improving the accuracy and reliability of the sensor, which is of great significance for preparing a new type of luminous pressure gauge with fast response speed and high accuracy in the low-pressure area.
[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an all-inorganic perovskite nanocrystalline composite material, characterized in that: The following steps are involved: (1) firstly mixing lead bromide and octadecene for a first heat treatment, and then adding oleic acid and oleylamine for a second heat treatment to obtain a lead bromide precursor solution; (2) mixing the lead bromide precursor solution obtained in step (1) with the cesium oleate solution to react, and cooling to obtain an all-inorganic perovskite nanocrystal mixed solution; (3) The all-inorganic perovskite nanocrystal mixed solution obtained in step (2) is mixed with zinc stearate and dodecanethiol for reaction, centrifuged, and the solvent is removed to obtain a product.
2. The method for preparing the all-inorganic perovskite nanocrystalline composite material according to claim 1, characterized in that: In the step (1), the mass volume ratio of lead bromide, octadecene, oleic acid and oleylamine is 0.06-0.08 g: 4-6 mL: 0.4-0.6 mL: 0.4-0.6 mL.
3. The method for preparing the all-inorganic perovskite nanocrystalline composite material according to claim 1, characterized in that: The conditions for the first heat treatment in step (1) are to keep the temperature at 100-150° C. for 30-90 minutes; and the conditions for the second heat treatment are to keep the temperature at 100-150° C. until the lead bromide is completely dissolved.
4. The method for preparing the all-inorganic perovskite nanocrystalline composite material according to claim 1, characterized in that: The cesium oleate solution in step (2) is prepared by the following method: cesium carbonate, octadecene and oleic acid are mixed and heat-treated to obtain the solution.
5. The method for preparing the all-inorganic perovskite nanocrystalline composite material according to claim 4, characterized in that: The mass volume ratio of the cesium carbonate, octadecene and oleic acid is 0.3-0.5 g:10-30 mL:1-2 mL.
6. The method for preparing the all-inorganic perovskite nanocrystalline composite material according to claim 4, characterized in that: The heat treatment conditions are: firstly keep the temperature at 110-130° C. for 30-90 minutes, and then keep the temperature at 140-160° C. until the cesium carbonate is completely dissolved.
7. The method for preparing the all-inorganic perovskite nanocrystalline composite material according to claim 1, characterized in that: In the step (2), the volume ratio of the lead bromide precursor solution to the cesium oleate solution is 4-8:0.1-0.3; the conditions for the mixed reaction are: firstly heating the lead bromide precursor solution to 180-190° C., keeping the temperature for 3-7 minutes, and then adding the cesium oleate solution to react for 30-90 seconds.
8. The method for preparing the all-inorganic perovskite nanocrystalline composite material according to claim 1, characterized in that: In the step (3), the mass volume ratio of the all-inorganic perovskite nanocrystal mixed solution, zinc stearate and dodecanethiol is 5-10 mL: 100-120 mg: 1-5 mL.
9. An all-inorganic perovskite nanocrystalline composite material, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the all-inorganic perovskite nanocrystal composite material according to claim 9 in the preparation of a pressure detector.
Citation Information
Cited By
Quantum dot light conversion packaging adhesive film and preparation method and application thereof
CN119979054A